The Constitutionality of the Constitutional Court's Role as a Negative Legislator: The Limits of the Constitutional Court's Authority in Judicial Review of Statutes Against the 1945 Constitution - Jefrianus Tamo Ama; Muhammad Junaidi; Endah Pujiastuti (Journal of General Education and Humanities, 2026)
The constitutional role of the Constitutional Court of Indonesia as a negative legislator has generated continuing scholarly debate, particularly regarding whether judicial decisions containing conditional interpretations amount to an exercise of positive legislative authority. However, no clear analytical framework has been consistently applied to distinguish constitutionally permissible constitutional interpretation from judicial law-making. This study examines the Constitutional Court's constitutional position as a negative legislator. It analyzes four landmark Constitutional Court Decisions No. 46/PUU-VIII/2010, No. 14/PUU-XI/2013, No. 91/PUU-XVIII/2020, and No. 90/PUU-XXI/2023 to determine the constitutional limits of judicial review under Article 24C of the 1945 Constitution of the Republic of Indonesia. Employing normative legal research with statutory, conceptual, and case approaches, the study analyzes primary, secondary, and tertiary legal materials using descriptive-analytical methods. The decisions are evaluated based on three analytical criteria: whether the Court merely invalidates unconstitutional statutory provisions, whether it formulates new legal norms or regulatory standards, and whether its reasoning substitutes for legislative policy choices. The findings demonstrate that the Constitutional Court constitutionally remains a negative legislator. Nevertheless, the degree of judicial intervention varies across the examined cases. While several decisions contain constitutional interpretations that guide future application of statutory provisions, not every conditional interpretation constitutes an exercise of positive legislative power. Rather, a decision should be regarded as reflecting positive-legislator characteristics only when the Court effectively creates new normative rules or replaces legislative policy choices. This study contributes an analytical framework for distinguishing legitimate constitutional interpretation from judicial law-making and argues that the Court's authority should continue to be exercised within the principles of judicial restraint, respect for open legal policy, and the constitutional limits established by Article 24C of the 1945 Constitution.